Consumer Perception Towards Electric Vehicle - Vashisth, Dr. Renu; Gupta, Ms. Jyoti (The journal of contemporary issues in business and government, 2021)
This paper includes what are the various factors that affect the overall perception of a consumer towards an EV and whether or not those factors have a relationship with the perception towards the electric vehicle. Also, this study includes topics like why should we switch to electric vehicle and what is the need for an electric vehicle and how should we adopt it and are we ready enough to adopt this technology in to our daily routine. And what are the various types of EV currently present and what all are the factors that directly influence an EV adoption in country like India. And when was first EV introduced and how does it grow from back then until now. In this study we also take into account the relationship between barriers and the perception towards EV and also to find out this we have used statistical tools and graphs, which are done using one factor ANOVA test. Also, some attributes related to the consumer are also taken into account and how they influence it perception and how these attributes affect the factors and barriers for the EV perception and adoption.